Analisis Inovasi Layanan E-Commerce pada Produk Kuliner Tradisional : Studi Kasus Penerapan Strategi Digitalisasi pada Usaha Soto Banjar Sawojajar-Kota Malang - Ayu Putriana Dewi; Agus Hermawan (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
The development of digital technology encourages traditional culinary business actors to adapt to e-commerce services in order to expand market reach and improve service efficiency. This study aims to analyze the digital innovation implemented by the Soto Banjar business in Sawojajar, Malang City, in facing challenges and opportunities in the digital era. Using a descriptive qualitative approach with a case study method, data was collected through interviews, observations, and documentation. The results of the study show that the integration of digital platforms such as GrabFood, ShopeeFood, Instagram, and WhatsApp has a positive impact on the effectiveness of promotions, ordering systems, and product distribution. Service innovations such as pre-order systems and attractive packaging help strengthen product image and increase customer satisfaction. Despite facing challenges such as digital promotion costs and spikes in demand, digital transformation has proven to be able to increase the competitiveness and sustainability of this traditional culinary business.